Cold hearts and dark minds: a systematic review and meta-analysis of empathy across dark triad personalities - Shukla, Meenakshi; Upadhyay, Niti (Frontiers in Psychiatry, 2025)
IntroductionThis systematic review and meta-analysis explored cognitive and affective empathy differences across Dark Triad traits—Narcissism, Machiavellianism, and Psychopathy.MethodsRegistered on PROSPERO and following PRISMA guidelines, PubMed, Scopus, Science Direct, ProQuest, and Google Scholar were searched for studies published until June 2024. Risk of bias was evaluated using Egger’s test and Rank correlation test, along with risk-of-bias plots (Robvis) for quality assessment.ResultsFourteen studies (N = 5,328) met the inclusion criteria. Meta-analysis showed Narcissism was negatively associated with affective empathy (r= -.134, p<.05) but not significantly linked to cognitive empathy (r= .061, p= .215), while Machiavellianism had a significant negative correlation with both cognitive (r= -.089, p<.05) and affective empathy (r= -.291, p<.0001). Psychopathy demonstrated the strongest negative association with affective empathy (r= -.347, p<.0001). Moderate-to-high heterogeneity was found across all analyses (I2 range: 40.56% - 94.03%).DiscussionThis review underscores differential empathy profiles across Dark Triad traits, with significant affective empathy deficits in Psychopathy and Machiavellianism and the complex role of cognitive empathy in Narcissism and Machiavellianism. Further research should examine situational and subtype -specific factors influencing empathy in Dark Triad traits to enhance theoretical understanding and inform interventions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024559533, identifier CRD42024559533.